Enhancing the halal potato chips supply chain: innovative risk mitigation strategies for sustainable growth - Mustaniroh, Siti Asmaul; Sucipto, Sucipto; Pujiastuti, Yuyun; Prabaningtias, Nadya; Saputri, Rita; Koentjoro, Maharani Pertiwi; Rahma, Rizka Aulia (Eastern-European Journal of Enterprise Technologies, 2025)
Consumer trust is an important asset in the distribution of the halal supply chain. The object of this research is the halal supply chain for micro-scale potato chip enterprises, involving suppliers, producers, and retailers. The final product’s halal status may be at risk caused by factors like sourcing raw materials, production processes, storage, distribution, and halal management at various supply chain phases. The problem to be solved is to develop a comprehensive institutional model of the potato chip supply chain, identify and assess these halal-related risks, map risk agents based on risk events, and develop alternative mitigation strategies to minimize potential threats. To accomplish this, an integrated methodology, including the House of Risk (HoR) and Interpretive Structural Modelling (ISM) methodologies, is implemented. The findings reveal the identification of 69 risk events and 70 risk agents, all associated with planning, purchasing, production, and distribution. Thirty priority risk agents requiring immediate attention were determined using the Pareto Diagram and ISM. Based on the ISM analysis, risk agents were categorized into independent and dependent variables within the potato chip business cluster. The integration of HoR and ISM effectively prioritizes risk agents and uncovers their interrelationships, enabling robust mitigation strategies. The approved approach provides a comprehensive risk assessment framework, allowing producers to control the main risk factors affecting halal product integrity, and enhance consumer trust. These findings are particularly valuable for micro-scale potato chip enterprises to strengthen their halal supply chain integrity, improve risk management practices, and increase competitiveness in halal markets